Genotypic variation in sunflower (Helianthus annuus) for salt tolerance - MURALIDHARUDU, Y; RAVISHANKAR, G; HEBBARA, M; PATIL, S G (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during winter season (rabi) 1995-96' . 1996-97 on 7 sunflower (Helianthus anmaus L.)genotypes for its tolerance to salinity under field conditions on sa. Vertisols (with a salinity gradient ranging from1.1 to 20 dS/m) of Tungabhadra Project area. The seed yield of sunflower genotypes was correlated.with time weightedmean salinity to compute yield maxima, threshold salinity and slope. 'CO 2', 'PAC 36' and 'PKVSH 27' sunflowerperformed better than other genotypes at higher salinity levels (> 8 dS/m). The genotypes 'PAC 308', 'CO 4' and 'EC68414' which were promising under marginally saline conditions (4-8 dS/m) suffered at higher salinity (> 8 dS/m).There was high correlation between the performance of genotypes under saline conditions in the field and laboratory.